The Urgency of Learning Coding for Elementary School Students in Indonesia - Putra, Ilzam Afdila; Nugroho, Agung Wahyu; Wakhudin, Wakhudin (Proceedings Series on Social Sciences & Humanities, 2025)
The rapid development of digital technology demands early coding education in elementary schools. Coding enhances students' logical thinking, creativity and problem-solving skills, preparing them for future challenges. This research explores the urgency of coding education in Indonesia through a qualitative literature review. Findings show that coding promotes computational thinking and 21st century skills. However, its implementation faces challenges, such as lack of teacher training, limited infrastructure and gaps in the curriculum. The government and education stakeholders should integrate coding into the primary school curriculum, provide training for teachers and develop supporting infrastructure. Addressing these challenges will ensure coding education benefits Indonesian students, equipping them for the digital age.